Impact of Combined Oral Zinc Sulfate and Phototherapy on Serum Bilirubin Levels in the Term Neonates with Jaundice - Shourangiz Beiranvand; Reza Hosseinabadi; Majid Firouzi; Mohammad Almasian; Khatereh Anbari (Mashhad University of Medical Sciences, 2018)
Background: Jaundice is a physiological phenomenon and common disorder in the neonatal period. Jaundice occurs in the first month of life in 60% of term and 80% of preterm neonates, leading to hospitalization. The present study aimed to determine the effect of oral zinc sulfate on serum bilirubin levels in the neonates undergoing phototherapy. Methods: This randomized clinical trial was conducted on 90 normal term neonates aged more than 24 hours with the total serum bilirubin of 14-19 mg/dc, who were admitted to the neonatal ward of Shahid Madani Hospital in Khorramabad, Iran for uncomplicated jaundice. Based on the inclusion criteria, these infants were divided into two groups of experimental (n=45) and control (n=45) via block random allocation. Infants in the control group only received phototherapy, and the experimental group received oral sulfate zinc (5 mg b.i.d.) in addition to phototherapy. Total serum bilirubin levels were measured upon admission and 24 and 48 hours after admission. Results: No significant differences were observed between the experimental and control groups in terms of age, gender, birth weight, hemoglobin level, reticulocyte percentage, and total serum bilirubin at the beginning of the study (P>0.05). Comparison of the bilirubin levels using repeated measures ANOVA at different times indicated significant differences in the neonatal serum values and blood cell counts between the study groups (time effect) (F=598.078; P